"الأهمية النسبية لأنشطة إدارة الإمداد في تحسين أبعاد الميزة التنافسية في المؤسسة الاقتصادية دراسة ميدانية لعينة من المؤسسات الصناعية في ولاية الوادي " - رجاء رحيمة, مجول; كنزة, قزون (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى الوقوف عند مستوى الأهمية المتعلقة بأنشطة الإمداد لمؤسسة صناعية متمثلة في إدارة الشراء، إدارة التخزين، إدارة الإنتاج، إدارة التوزيع، في مجال تحسين التنافسية المبنية على أحد مصادرها المتمثلة في مستوى سعر وجودة الخدمات المقدمة، وكذا والوقت والمرونة اللذان يتعلقان بظروف تقديم المنتجات لمختلف الشرائح المستهدفة من العملاء. واعتمدت الدراسة في استخلاص نتائجها على جانب ميداني تعلق بعينة من المؤسسات الصناعية العاملة بإقليم ولاية الوادي من خلال إطاراتها العاملين على مستوى الإدارة العليا لها، وتم تحليل البيانات المجمعة بناء على تقييم مفردات عينة الدراسة استعانة بالبرنامج الاحصائي SPSSإصدار 25. الكلمات المفتاحية: المؤسسة الصناعية، إدارة الإمداد، التنافسية، أنشطة الإمداد، الميزة التنافسية. "" This study aims to position itself at the level of importance associated with the supply activities of an industrial company represented in purchasing management, warehouse management, production management and distribution management, in the field of improving competitiveness. By relying on one of its sources of the price level and quality of services provided, as well as time and flexibility related to the terms of supplying products to the various target segments of customers. The study relied on extracting its results from a field aspect related to a sample of industrial establishments operating in El-ouad Governorate through its employees working at the level of its senior management, and the collected data were analyzed based on vocabulary assessment. A sample of the study using the statistical program SPSS version 25. Key words: Industrial organization, supply management, competitiveness, supply activities and competitive advantage. "
ماستر اقتصاد
Keywords: لمؤسسة الصناعية، إدارة الإمداد، التنافسية، أنشطة الإمداد، الميزة التنافسية.; Industrial organization, supply management, competitiveness, supply activities and competitive advantage.